Attenuation of clinical and immunological outcomes during SARS‐CoV‐2 infection by ivermectin. Issue 8 (12th July 2021) - de Melo, Guilherme Dias; Lazarini, Françoise; Larrous, Florence; Feige, Lena; Kornobis, Etienne; Levallois, Sylvain; Marchio, Agnès; Kergoat, Lauriane; Hardy, David; Cokelaer, Thomas; Pineau, Pascal; Lecuit, Marc; et al.
Abstract: The devastating pandemic due to SARS‐CoV‐2 and the emergence of antigenic variants that jeopardize the efficacy of current vaccines create an urgent need for a comprehensive understanding of the pathophysiology of COVID‐19, including the contribution of inflammation to disease. It also warrants for the search of immunomodulatory drugs that could improve disease outcome. Here, we show that standard doses of ivermectin (IVM), an anti‐parasitic drug with potential immunomodulatory activities through the cholinergic anti‐inflammatory pathway, prevent clinical deterioration, reduce olfactory deficit, and limit the inflammation of the upper and lower respiratory tracts in SARS‐CoV‐2‐infected hamsters. Whereas it has no effect on viral load in the airways of infected animals, transcriptomic analyses of infected lungs reveal that IVM dampens type I interferon responses and modulates several other inflammatory pathways. In particular, IVM dramatically reduces the Il‐6/Il‐10 ratio in lung tissue and promotes macrophage M2 polarization, which might account for the more favorable clinical presentation of IVM‐treated animals. Altogether, this study supports the use of immunomodulatory drugs such as IVM, to improve the clinical condition of SARS‐CoV‐2‐infected patients. SYNOPSIS: COVID‐19, caused by SARS‐CoV‐2, induces airways and pulmonary symptoms, and in severe cases can lead to respiratory distress and death. This study shows that the modulation of the host's inflammatory response using ivermectin as a repurposed drug, independently of the viral load, strongly diminished the clinical score and severity of the disease (including anosmia) observed in SARS‐CoV‐2‐infected golden hamsters. This study brings the proof‐of‐concept that a chemical therapy using ivermectin can preserve the clinical condition by modulating the inflammatory response, even without antiviral activity. The clinical presentation is directly linked to inflammation and not necessarily to viral load. A chemical therapy by ivermectin induces a sex‐dependent and compartmentalized response, preventing clinical deterioration and reducing olfactory deficit. Ivermectin limits the response of several signaling pathways related to that of type I/III interferon, cytokines activation and inflammatory cells population in infected lungs. A reduced Il‐6/Il‐10 ratio in the lung might account for a more favorable clinical presentation. Ivermectin‐treated animals presented a M2 polarization of myeloid cells recruited to the lung. Abstract : COVID‐19, caused by SARS‐CoV‐2, induces airways and pulmonary symptoms, and in severe cases can lead to respiratory distress and death. This study shows that the modulation of the host's inflammatory response using ivermectin as a repurposed drug, independently of the viral load, strongly diminished the clinical score and severity of the disease (including anosmia) observed in SARS‐CoV‐2‐infected golden hamsters. This study brings the proof‐of‐concept that a chemical therapy using ivermectin can preserve the clinical condition by modulating the inflammatory response, even without antiviral activity.